INVESTIGASI KERUNTUHAN SEBAGIAN STRUKTUR BETON LANTAI 2 PADA PROYEK PEMBANGUNAN DAN REHABILITASI PASAR X - Trias Rahardianto, Suhariyanto (Prokons: Jurnal Teknik Sipil, 2014)
Partial collapse of Concrete Structure at 2nd Floor of the Development and Rehabilitation Project Market X, occurred during heavy rain and strong winds conditions. Reconstructively, the collapse of second floor area confined by D, G, 5 and 9 lines, are indicated as the result of domino effect of the collapse preceded by the collapse of the beam midspan along the line of F7-F8. Some factors suspected as the cause of the collapse; the weakness of the composite action of concrete and its reinforcement, and the lack of reinforcement detailing implemented at most structural elements. Action plan that needed be done is temporer retrofitting, demolitioning and cleaning up the wastes. reworking on collapsed structure,  repairing and reinforcing some poor structural elements. In addition, the adequacy of concrete cover depth is also need attention, due to the location of the X market which is in the corrosive environment, therefore a guarantee of preventing steel reinforcement from corrosion is required  for it will greatly affect to the strength of concrete structures.Keywords: concrete structure, Reconstructive, domino effect, composite action, detailing